O impacto da Olimpíada de Matemática em alunos da escola pública - Alves, Washington José Santos (2010)
This dissertation aims to investigate Brazilian Mathematical Olympiad Public Schools - OBMEP, sponsored by the federal government since 2005. The OBMEP was inserted into the scenario of Brazilian education in order to promote stimulus to the study of mathematics by students and contribute to improving the quality of basic education schools of local, state and federal. To understand the analysis proposed by the organizing committee of the association, we made a qualitative study with students from 3rd grade of high school, a public school located in São Paulo, to analyze how the OBMEP can stimulate and promote the study of mathematics among public school students and what possible contributions that evaluation can play in improving the quality of basic education in the country. Data analysis revealed that there is student interest in acquiring new knowledge and they are not motivated to participate in OBMEP due to lack of information about the competition